2021
DOI: 10.3390/agronomy11040694
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Impact of Rice Cultivation and Off-Season Period on Dynamics of Soil Enzyme Activities and Bacterial Communities in Two Agro-Ecological Regions of Mozambique

Abstract: Soil ecosystem perturbation due to agronomic practices can negatively impact soil productivity by altering the diversity and function of soil health determinants. Currently, the influence of rice cultivation and off-season periods on the dynamics of soil health determinants is unclear. Therefore, soil enzyme activities (EAs) and bacterial community compositions in rice-cultivated fields at postharvest (PH) and after a 5-month off-season period (5mR), and fallow-fields (5-years-fallow, 5YF; 10-years-fallow, 10Y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 145 publications
0
2
0
Order By: Relevance
“…In fact, a positive correlation of CH 4 emission with the activity of UR was observed (r = 0.681, p < 0.01). The process starts as urea processing by microorganisms imply C consumption, thus causing the emission of CH 4 [46]. Such a process was strongly enhanced when the application of N fertilizer was preceded by the organic amendment (C-TPOW).…”
Section: Emissions Chmentioning
confidence: 99%
“…In fact, a positive correlation of CH 4 emission with the activity of UR was observed (r = 0.681, p < 0.01). The process starts as urea processing by microorganisms imply C consumption, thus causing the emission of CH 4 [46]. Such a process was strongly enhanced when the application of N fertilizer was preceded by the organic amendment (C-TPOW).…”
Section: Emissions Chmentioning
confidence: 99%
“…The construction of bacterial ecological networks can reveal information regarding community efficiency, complexity, and the role of keystone phylotypes [78]. The two networks found in this study were non-random and differ between fire regimes.…”
Section: New Insights From Miombo Bacterial Ecological Networkmentioning
confidence: 73%
“…Chloroflexi are facultative anaerobic and have a recognized role as heterotrophic oligotrophs in soils, having the ability to survive on recalcitrant plant polymers [47] [48]. In the agroecosystems, Actinobacteria contribute to nutrient cycling and the degradation of organic compounds, including pesticides and herbicides [49] [50] [51] [52]. For archaea, the relative abundance revealed that, the preponderant class was Methanomicrobia followed by Methanobacteria, Thaumarchaeota and Crenarchaeota which all accounted for an average of 80% of the total archaeal sequences in the irrigated rice field.…”
Section: Relative Abundance Of Bacterial and Archaeal Communitiesmentioning
confidence: 99%